2001
DOI: 10.1002/1521-3951(200102)223:3<821::aid-pssb821>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Review of Emission and Lifetime Data Concerning Cu+ Fluorescence in Alkali Halides

Abstract: A review of the relevant data concerning the decay properties of the Cu þ fluorescence in alkali halides is presented. A critical analysis of the experiments reported in literature shows that the problem of the correct and complete interpretation of the Cu þ fluorescence was made complicated in the past essentially because of historical reasons. The validity of the decay models was ascertained by the authors by simultaneously detecting both lifetime and quantum yield during each set of measurements as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The existence of both considered models in Cu-doped alkali-halides has been discussed in works [6,[10][11][12]. In our opinion, both of these models can be realized also in CsBr:Cu and CsBr:CuBr 2 crystals.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of both considered models in Cu-doped alkali-halides has been discussed in works [6,[10][11][12]. In our opinion, both of these models can be realized also in CsBr:Cu and CsBr:CuBr 2 crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the validity of the Pedrini decay model for cu+ (as well as for Ag+ and Au+) has been verified by simultaneously detecting both lifetime and quantum yield during each set of measurements as a function of temperature [2]. In particular, it has been found that Eq.…”
mentioning
confidence: 93%
“…We showed in a review (2] that the best explanation of the cu+ de-excitation mechanism was done by Pedrini, who initially investigated the fluorescence in LiCI [3] and in NaCI [4],where cu+ is respectively hannonic and anharmonic on-centre in the GS, and then extended his study to several hosts containing either Cu+ or Ag+ impurity. Pedrini assumed the existence of a metastable level lying just under the emitting level.…”
mentioning
confidence: 99%
See 2 more Smart Citations